2018
DOI: 10.1155/2018/1875928
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Yokukansan as a Remedy for Parkinson’s Disease

Abstract: Parkinson's disease (PD), the second most common progressive neurodegenerative disorder, is characterized by complex motor and nonmotor symptoms. The clinical diagnosis of PD is defined by bradykinesia and other cardinal motor features, although several nonmotor symptoms are also related to disability, an impaired quality of life, and shortened life expectancy. Levodopa, which is used as a standard pharmacotherapy for PD, has limitations including a short half-life, fluctuations in efficacy, and dyskinesias wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 84 publications
(160 reference statements)
0
3
0
Order By: Relevance
“…Recently, another herbal medicine, YKS, was reported to be effective for treating idiopathic RBD ( 25 ). In preclinical studies, YKS has been shown to regulate neurotransmitters, including γ-aminobutyric acid, serotonin, glutamate, and dopamine; regulate the expression of dynamin and glutamate transporters; and regulate the levels of glucocorticoid hormones and related enzymes, such as choline acetyltransferase and acetylcholinesterase ( 26 ). YKS consists of seven crude drugs, none of which are shared by KRB.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another herbal medicine, YKS, was reported to be effective for treating idiopathic RBD ( 25 ). In preclinical studies, YKS has been shown to regulate neurotransmitters, including γ-aminobutyric acid, serotonin, glutamate, and dopamine; regulate the expression of dynamin and glutamate transporters; and regulate the levels of glucocorticoid hormones and related enzymes, such as choline acetyltransferase and acetylcholinesterase ( 26 ). YKS consists of seven crude drugs, none of which are shared by KRB.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been conducted on the effects and mechanisms of Ukgansan and its herbal ingredients to confirm its potential application in the treatment of neurological diseases, including PD [ 40 ]. It was also reported that the multiple potential actions of Ukgansan in PD were explained through neurotransmissions, such as glutamate and dopamine, and mechanisms such as neuroprotection, neuroplasticity promotion, and the anti-effects of stress and inflammation [ 17 , 21 , 40 ]. Ukgansan was reported to have neuroprotective effects on dopaminergic neurons from toxicity caused by MPP+/MPTP and improved motor function by activating phosphatidylinositol 3-kinase (PI3K)/Akt.…”
Section: Discussionmentioning
confidence: 99%
“…The program was planned for eight weeks with each session lasting 180 minutes. The program was prepared by the researcher using many sources (Allen, 2017;Demir, 2017;Jalambadani, Borji, & Bakaeian, 2020;Jang et al, 2018;Peterson & Rappaport, 2014).…”
Section: Sessionsmentioning
confidence: 99%